2015
DOI: 10.1080/16078055.2015.1075899
|View full text |Cite
|
Sign up to set email alerts
|

Home brewing and serious leisure: exploring the motivation to engage and the resultant satisfaction derived through participation

Abstract: The study examines what motivates an individual to engage in a serious leisure activity and the depth of the satisfaction derived through participation. The study examines the topic through the lens of home craft beer brewers filtered through Stebbins' serious leisure construct (1982). The data were collected through a yearlong immersion with a local brewing club chapter, extensive indepth interviews with two key informants, and a survey instrument (n = 4207) that collected both quantitative and qualitative da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…Heo, Lee, McGormick, & Pedersen, 2010;Korpela & Kinnunen, 2010;Cuenca, Kleiber, Monteagudo, Linde, & Jaumot-Pascual, 2014;Liu, 2014;Pi, Lin, Chen, Chiu, & Chen, 2014;Liu & Yu, 2015;Stebbins, 2015). Additionally, hobbies positively affect an individual's experience of satisfaction (Murray & O'Neill, 2015). In research on hobbies and their effects on subjective well-being, one of the identified mechanisms has been recovery from work demands and work stress (e.g.…”
mentioning
confidence: 99%
“…Heo, Lee, McGormick, & Pedersen, 2010;Korpela & Kinnunen, 2010;Cuenca, Kleiber, Monteagudo, Linde, & Jaumot-Pascual, 2014;Liu, 2014;Pi, Lin, Chen, Chiu, & Chen, 2014;Liu & Yu, 2015;Stebbins, 2015). Additionally, hobbies positively affect an individual's experience of satisfaction (Murray & O'Neill, 2015). In research on hobbies and their effects on subjective well-being, one of the identified mechanisms has been recovery from work demands and work stress (e.g.…”
mentioning
confidence: 99%
“…The study therefore contributes empirically and theoretically to the leisure literature, first, by examining home brewers, and second, by adopting the above theoretical frameworks and by proposing a refinement in the context of home brewing. Apart from two very recent studies conducted in the United States (Murray & O'Neill, 2015) and the United Kingdom (Thurnell-Read, 2016), home brewing has received very limited attention from the leisure literature. The present research provides a component of originality, by focusing on home brewers engaged in this activity in Australia.…”
Section: Methodsmentioning
confidence: 99%
“…First, the characteristics of home brewing undoubtedly emphasise the importance of collaborating in producing quality and variety of beers. Such importance is reflected in home brewers' involvement sampling beers or participating in home brewing competitions (Murray & O'Neill, 2015) to showcase their craft beers. These characteristics strongly suggest that improvement, for instance, of knowledge, techniques and practices, ultimately leading to the final product, is one key aspect illustrating home brewers' 'problem domain' (Wood & Gray, 1991).…”
Section: Figure 1 Herementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, values 4) guide the Schwartz's (1994) values, and associates these with dimensions related to commercial craft brewing (Table 1). These dimensions are identified in one of the very few studies to date, in which Murray and O'Neill (2015) explored main motivations and satisfaction based on Stebbins' (1982) serious leisure construct among home (noncommercial) brewers in the United States.…”
Section: Universal Values Modelmentioning
confidence: 99%